Exploring treatment models for oligometastatic castration-sensitive prostate cancer: evolution of therapeutic strategies - Xu, Haizhong; Guo, Jialin; Peng, Wenrui; Wang, Jianqiang; Shi, Longlong; Yang, Xukai (Frontiers in Oncology, 2026)
Oligometastatic castration (hormone)-sensitive prostate cancer (omCSPC) represents an intermediate disease state between localized and widely metastatic cancer. This review synthesizes current evidence on diagnosis, treatment, and biomarkers in omCSPC to guide personalized therapeutic strategies and improve clinical outcomes. A comprehensive literature review was conducted, focusing on the role of PSMA-PET/CT in lesion detection, evolving local and systemic treatment modalities, and the prognostic and predictive value of biomarkers in omCSPC.PSMA-PET/CT has improved the precision of oligometastatic lesion identification. Treatment of omCSPC has evolved from Androgen Deprivation Therapy (ADT) alone to combination regimens incorporating novel hormonal agents or chemotherapy. Local therapies, including radiotherapy and surgery, are increasingly utilized and may delay disease progression. omCSPC exhibits clinical and molecular heterogeneity, with several emerging biomarkers showing prognostic potential, though standardization is still needed. The management of omCSPC requires a multidisciplinary approach and personalized treatment strategies. Further research into biomarkers and the optimal integration of local therapies is essential to improve patient quality of life and long-term survival.